The effects of land transfer marketization on the urban land use efficiency: An empirical study based on 285 cities in China - Xu Jiang (Elsevier, 2021)
The market-oriented allocation reform of urban land resources has become an important component of economic system reform in China, while its objective impact on land use efficiency still remains uncertain and needs to be revealed somehow. Based on the panel data of 285 cities in China from 2003 to 2015, this study uses the DEA method to measure the urban land use efficiency firstly, and then the spatial Durbin model is adopted to examine the spatial effects of land transfer marketization on urban land use efficiency in China. The results show that land transfer marketization can significantly improve urban land use efficiency of the local region at 0.16% on the one hand, while on the other hand it has an inhibitory effect on urban land use efficiency of the spatial related regions at a relatively higher level of 0.17%. Besides, there exists club convergence of the urban land use efficiency of sample cities in China. As for other variables affecting the urban land use efficiency spatially, economic development level, industrial structure and population scale have a significantly promoting effect at the level of 0.1263, 0.1667 and 0.1735 respectively, while infrastructure level and opening degree may have an inhibitory effect because of their irreconcilable stages, though most of them failed the significance test. On the basis of these theoretical and empirical analyses, some policy recommendations such as adhering to the market-oriented land transfer policy, strengthening the communication and coordination mechanism between regions are provided to policymakers in order to make the most use of land resources.